Measuring foreign impact: leading index construction using hierarchical dynamic factor model - Agne Reklaite (Baltic Journal of Economics, 2016)
In this paper a new method of constructing the leading economic index is presented. Its main advantage is the ability to distinguish domestic and foreign factors influencing the growth of economy and it is performed via dynamic hierarchical factor modelling. An application is carried out with Lithuanian data and the results indicate that foreign component corresponds to an economically and statistically significant amount of variance. Under this new methodology, a hypothesis that the effect of international trends on the growth of economy is increasing over time is validated. Results indicate that globalization effect can be quantified and monitored using the proposed decomposition.
Keywords: C43; E32; C10; 330; Coincident and leading indicators; hierarchical dynamic factor model; small open economy; globalization